A new genus and species of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) parasitoid of Euxesta eluta Loew (Diptera, Otitidae) attacked Bt sweet corn in Argentina - Gallardo, Fabiana Edith (2017)
Fil: Gallardo, Fabiana Edith. División Entomología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina